Pengaruh Konten Promosi Digital UMKM Kuliner terhadap Keputusan Pembelian Mahasiswa UINSU (Lembaga Pengembangan Kinerja Dosen, 2026)
The motivation for this study stems from the rapid development of digital marketing within small and medium-sized enterprises (SMEs) in the food industry, aimed at attracting customers, particularly the student demographic who frequently utilise social media. The research objective is to identify the digital marketing messages influencing purchasing decisions among UINSU students. Employing a quantitative methodology, this study surveyed 30 UINSU students via questionnaire distribution. Data were processed using SPSS version 31, encompassing validity and reliability assessments, literature review, univariate analysis, and inferential statistics. Findings indicate that digital information holds significant value for UINSU students' purchase intentions, with a conversion rate of 0.508 (equivalent to 50.8%). This implies that digital marketing messages contribute 50.8% to purchase intention, with the remaining 49.2% influenced by external factors not considered in this study. Based on these findings, it can be concluded that the more appealing and effective the digital marketing messages employed by SMEs in the food and beverage industry, the more significant their influence on consumer purchase intention.